2019
DOI: 10.1002/cam4.2259
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of 547 patients with neuroendocrine tumors in a Chinese population: A single‐center study

Abstract: Background Neuroendocrine tumors (NETs) are rare, which has resulted in a lack of published data on their epidemiology and clinical features. We therefore aimed to investigate the epidemiology, clinical features, treatments, and prognosis of patients with NETs. Methods The clinicopathologic characteristics of 547 patients who were pathologically diagnosed with NETs were retrospectively analyzed, including age, sex, primary and metastatic sites, symptoms, pathology, trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…In the SEER database, the rectum and small intestine are the most common sites of GEP-NENs [2,3]. Our results showed that the pancreas, rectum and stomach were the most common sites, which were consistent with the results of a large retrospective single-center study in China [17]. We found that the metastasis rate of patients with GEP-NENs was 39.9%, and the most common site of distant metastasis was the liver.…”
Section: Discussionsupporting
confidence: 89%
“…In the SEER database, the rectum and small intestine are the most common sites of GEP-NENs [2,3]. Our results showed that the pancreas, rectum and stomach were the most common sites, which were consistent with the results of a large retrospective single-center study in China [17]. We found that the metastasis rate of patients with GEP-NENs was 39.9%, and the most common site of distant metastasis was the liver.…”
Section: Discussionsupporting
confidence: 89%
“…(24). However, some reports have indicated that small tumors can recur or metastasize, and as tumor size was not significantly associated with the prognosis of NF-PNETs (17,25,26). Consistent with the previous reports, 3 of 28 small tumors in our study recurred and metastasized.…”
Section: Risk Of Malignancy Of the Nf-pnetssupporting
confidence: 88%
“…It was the small intestine, rectum, and pancreas in the United States, and the small intestine, appendix, and pancreas in Norway. 12 In another study conducted in our country, the most common primary site was the stomach (36.7%). This was followed by the pancreas (30.5%), small intestine and appendix (15.6%), and colon (7%).…”
Section: Discussionmentioning
confidence: 88%